A Numerical Simulation for Fusion Reaction in Tokamak D-T Plasma. (17th February 2021) - Zeng, Bo; Zhao, Zijia; Chen, Zhong; Pan, Dongmei; Lv, Zhongliang; Ma, Yanyun
Abstract: Fusion power, which generates electricity from the heat of fusion reactions, has the potential to solve the future energy crisis; hence, methods have been developed to study fusion reactions in a fusion reactor. For neutronic analyses of a fusion reactor, the reaction rate should be precisely calculated. The traditional calculation method has some defects. First, the deuterium-tritium fusion reaction cross-section data used are of the semiclassical model described by Gamow theory, which provides relatively accurate cross sections at energies below several hundreds of kilo-electron-volts in a center-of-mass frame. However, when energies increase, the data may be inaccurate. The ENDF/B-VI database provides accurate energies below 30 MeV. Since tokamak research always aims to raise the temperature inside, the ENDF/B-VI database may be more accurate at high temperatures and fit the research better. Second, adjacent plasmas with different temperatures and densities may influence each other and finally influence the reaction rate, which is not taken into account in the traditional calculation method. In this work, a numerical algorithm based on the ENDF/B-VI database employs both the Monte Carlo method and the discrete ordinates (SN ) method, which is used to simulate the transportation process to obtain more accurate reaction rate results. Parameters of the European demonstration fusion power plant (DEMO) A-mode are used to calculate the reaction rate by both the traditional method and the new algorithm. The differences of the results are shown, and the total reaction rate of the new algorithm is 4.23% higher than that of the traditional method.